Pelatihan Pembuatan Komik Digital sebagai Modifikasi Media Pembelajaran di SD Negeri Tangerang 2 - Lina Yuliana; Titi Warsiyati; Yoyoh Munirah; Wiwi Nurhidayah; Neneng Siti Zulaiha; Musringudin Musringudin (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2024)
Learning media is one of the resources that supports the creation of interesting and fun student learning conditions. Teachers must keep up with the development of interactive digital learning. This is one of the challenges for teachers in following technological developments to modify learning that is more attractive to students. Learning media that contain illustrated stories that present information by containing character figures are called comics. Comics can be used to convey information in a way that is popular and easy to understand. Comics combine the power of pictures and words, and organize them into a story line so that information is more easily absorbed. The implementation method in community service goes through three stages, the preparation, implementation and evaluation. The results obtained from this community service are that the training participants feel helped by this training. Participants who found it easy to creating comic learning media, after attending the training 92,3%. This means that there was an increase in the participants ability to use create comic learning media. After this training it is hoped the participants can apply the creation of comic learning media in the daily teaching and learning process at school.